Information Technology Training Based on the Siforterpadu Application to Improve Skills In M aking Financial Reports at BKM Sejahtera M andiri Cooperative - Migut Fitriani; Agus Efendi; Roemintoyo Roemintoyo (Universitas Sebelas Maret, 2023)
The skills of cooperative managers must be improved in using information technology to produce reliable financial statements. The purpose of this study is to determine how effective information technology training based on Siforterpadu applications is in improving the ability of BKM Sejahtera Mandiri Cooperative members to make financial statements. This research uses an experimental method, a pretest-posttest design, and questionnaire distribution to collect data. The research sample was selected through the purposive sampling technique, consisting of six participants. The results of this study indicate that information technology training based on Siforterpadu Applicati on has succeeded in improving the ability to utilize information technology, efficiency in preparing financial reports, and awareness of the importance of self-development for financial managers in BKM Sejahtera Mandiri cooperative. This training provides benefits for financial managers by making them more efficient and effective.